The suggestive technologies as a condition of vocational training of the teacher of music (Pedagogy of Higher and Secondary Education, 2007)
In article application the suggestive technologies which promote successful mastering of the realized and not realized components of mentality during mastering a material is considered. Use auto-trainings, various kihtl.s of meditations for development of emotional - shaped sphere is offered.
Keywords: vocational training; suggestive, technologies; auto-training; meditation; uture teacher of music